2008
DOI: 10.1016/j.jmb.2008.02.057
|View full text |Cite
|
Sign up to set email alerts
|

TRPM7 Regulates Myosin IIA Filament Stability and Protein Localization by Heavy Chain Phosphorylation

Abstract: Deregulation of myosin II-based contractility contributes to the pathogenesis of human diseases, such as cancer, which underscores the necessity for tight spatial and temporal control of myosin II activity. Recently, we demonstrated that activation of the mammalian α-kinase TRPM7 inhibits myosin II-based contractility in a Ca 2+ -and kinase-dependent manner. However, the molecular mechanism is poorly defined. Here, we demonstrate that TRPM7 phosphorylates the COOHtermini of both mouse and human myosin IIA heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
98
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 53 publications
3
98
0
1
Order By: Relevance
“…Studies have found that the TRPM7 channel regulates breast cancer cell proliferation, and TRPM7 is over-expressed in breast carcinoma tissue and is positively correlated with the Ki67 mitosis marker (27). Some studies have found that TRPM7 influences cell adhesion and migration via the regulation of myosin-IIA filament stability and that it influences protein localization by phosphorylating the heavy chain (28). However, one study found that mitogenactivated protein kinase (MAPK) signaling pathways are involved in the TRPM7-mediated migration and invasion of MDA-MB-435 breast cancer cells.…”
Section: Trp Channels and Breast Cancermentioning
confidence: 99%
“…Studies have found that the TRPM7 channel regulates breast cancer cell proliferation, and TRPM7 is over-expressed in breast carcinoma tissue and is positively correlated with the Ki67 mitosis marker (27). Some studies have found that TRPM7 influences cell adhesion and migration via the regulation of myosin-IIA filament stability and that it influences protein localization by phosphorylating the heavy chain (28). However, one study found that mitogenactivated protein kinase (MAPK) signaling pathways are involved in the TRPM7-mediated migration and invasion of MDA-MB-435 breast cancer cells.…”
Section: Trp Channels and Breast Cancermentioning
confidence: 99%
“…Mammals express six multidomain proteins with ␣-kinase domains (12). These include TRPM6 and TRPM7, which function as divalent cation channels and phosphorylate the tail of non-muscle myosin II (18,19) and eEF2K, which regulates protein synthesis (20).…”
mentioning
confidence: 99%
“…The authors also discovered that TRPM7 could directly complex with both β-actin and myosin IIA, and cause phosphorylation of the latter at the COOH-terminus. 101,102 Furthermore, the same group determined that such substrate identification and subsequent phosphorylation was greatly enhanced in the presence of TRPM7 autophosphorylation. 115 Another group employed the use of inducible TRPM7 overexpression in HEK-293 cell lines to study its potential ability in regulating members of the calpain protease family during cell adhesion.…”
Section: Trpm7 and The Cytoskeletonmentioning
confidence: 98%
“…The resourceful use of various TRPM7 channel and kinase mutants during past studies in cell lines may provide a viable means to approach questions regarding regionspecific roles in neurons. 101,102,115,116,118,119 Another important factor to consider when assessing ischemic-dependent TRPM7 activation is the putative role of environmental pH. It is widely accepted that ischemia and its ensuing cellular damage is associated with a reduction in pH levels.…”
Section: Trpm7 and The Cytoskeletonmentioning
confidence: 99%